Public Involvement in Environmental Issues with Reference to Jajahan Kuala Krai, Kelantan - Ismail, Mohammad Ghazi; Abdul Rahman, Haliza (Journal of Techno-Social, 2011)
Environmental problems are very serious and complex to be resolved through science approach, technical and legislation solely. Hence, the inclucive and active involvement and participation of civil is wanted. Civil society is inter parties interested and sure they involved directly with every planned development project and practiced at area they. Earlier study has proven that public societal involvement in environmental issue is still low and minimum. The study conducted in Jajahan Kuala Krai, Kelantan is intended to find out how far population knowledge in study area on environmental issues and the level of involvement the in said issue. This study involved 174 respondents. The study between demographic factor with respondent knowledge in environmental issues shows that is a significant relationship between respondent income and education with value of p respectively 0.039 and 0.036. The association between demographic factor with respondent’s knowledge in local environmental issue on the other hand shows that there are significant relationship between gender, age, income, education and resident period with the value of p respectively 0.045, 0.000, 0.029, 0.046 and 0.000. For demographic factor in association with environmental issues, has shown that there is a significant relationship between age, income, education and resident period with the value of p respectively 0.036, 0.041, 0.001 and 0.001. The results that found respondent income factor and education did influence on respondents knowledge level and involvement in environmental issues. As a conclusion, an actively engaged society in related environmental issues is very important due to the assurance of environmental quality that always will be protected.